Palbociclib Plus Fulvestrant or Everolimus Plus Exemestane for Pretreated Advanced Breast Cancer with Lobular Histotype in ER+/HER2− Patients: A Propensity Score-Matched Analysis of a Multicenter Retrospective Patient Series † - Orlandi, Armando (J Pers Med, 2020)
Cyclin-dependent kinase 4/6 inhibitors (CDK4/6i) in combination with endocrine therapy (ET) show meaningful efficacy and tolerability in patients with metastatic breast cancer (MBC), but the optimal sequence of ET has not been established. It is not clear if patients with lobular breast carcinomas (LBC) derive the same benefits when receiving second line CDK4/6i. This retrospective study compared the efficacy of palbociclib plus fulvestrant (PALBO–FUL) with everolimus plus exemestane (EVE–EXE) as second-line ET for hormone-resistant metastatic LBC. From 2013 to 2018, patients with metastatic LBC positivity for estrogen and/or progesterone receptors and HER2/neu negativity, who had relapsed during adjuvant hormonal therapy or first-line hormonal treatment, were enrolled from six centers in Italy in this retrospective study. A total of 74 out of 376 patients (48 treated with PALBO–FUL and 26 with EVE–EXE) with metastatic LBC were eligible for inclusion. Progression-free survival (PFS) was longer in patients receiving EVE–EXE compared with PALBO–FUL (6.1 vs. 4.5 months, univariate HR 0.58, 95% CI 0.35–0.96; p = 0.025). On the propensity score (PS) analysis, PFS was confirmed to be significantly longer for patients treated with EVE–EXE compared to PALBO–FUL (6.0 vs. 4.6 months, p = 0.04). This retrospective analysis suggests that EVE–EXE is more effective than PALBO–FUL for second line ET of metastatic LBC, allowing us to speculate on the optimal therapeutic sequence.